FEATURES OF THE USE OF NEURAL NETWORKS IN THE DESIGN OF UAVS FOR FLIGHT IN THE STRATOSPHERE - Kharchenko, Volodymyr; Onishchenko, Alexander (Proceedings of National Aviation University (archive), 2021)
Problems of application of neural networks during UAV design, and also questions of development of methods and algorithms of synthesis of neural network.